2001
DOI: 10.1007/s004240000464
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity of energy turnover in the heart

Abstract: Local myocardial blood flow varies substantially in spite of a rather homogeneous morphology. To further elucidate this paradox, the spatial heterogeneity of tricarboxylic acid cycle turnover (J(TCA), micromol min(-1) g(-1)) and coronary flow was assessed at a high spatial resolution (6x6x6 mm3) in the open chest dog. Local flow differed more than 2.5-fold between individual samples in each heart (n=7). Out of 1,500 myocardial samples, 1/10 received less than 60% and another 1/10 more than 138% of the normaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…On the basis of the sequential application of microspheres, early studies demonstrated that a temporal flow difference in a given region was relatively small compared with a spatial flow difference. Thus the distribution of regional myocardial flows has been considered quite stable (25,37,45), matching with local energy turnover and gene/ protein expression (11,27,39). However, at the presently focused microvascular levels, temporal fluctuations of regional flows seem to be comparable in magnitude to spatial flow variations as shown in CV and CA differences between bloodbolus-and blood-60 s-perfused hearts.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the sequential application of microspheres, early studies demonstrated that a temporal flow difference in a given region was relatively small compared with a spatial flow difference. Thus the distribution of regional myocardial flows has been considered quite stable (25,37,45), matching with local energy turnover and gene/ protein expression (11,27,39). However, at the presently focused microvascular levels, temporal fluctuations of regional flows seem to be comparable in magnitude to spatial flow variations as shown in CV and CA differences between bloodbolus-and blood-60 s-perfused hearts.…”
Section: Discussionmentioning
confidence: 99%
“…Fits with the full multiplet model were only accepted when the overall coefficient of variation (CV) was Ͻ25%. In case, this multiplet method did not lead to an acceptable fit of the model to the peak data because of low multiplet intensity relative to the NMR noise, we applied the simplified strategy to estimate J TCA by fitting the mean of the G2 and G3 peaks, divided by the total of the G4 peaks [ratio method (12,41); FC2 ϭ 0.6]. The value of glutamate was fixed at the biochemical assay value.…”
Section: Methodsmentioning
confidence: 99%
“…A similar method has recently been applied to demonstrate that regions with the 10% highest flow have significantly higher V O 2 than regions with the 10% lowest flow in the canine left ventricle (12). In this study, we applied our new 13 C method to measure the profile of V O 2 in small tissue areas in the normal in situ porcine left ventricle for the full range of blood flow.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In one dog, differently colored fluorescent microspheres (15 m, 250,000/kg) were then applied on days 1-3 via the atrial catheter while blood was simultaneously withdrawn from the aorta (10 ml/ min) into a virtual reference organ. For cardiac excision, the animal was anesthetized as previously described (10). In the other dog, radioactive microspheres were applied for local flow determinations in the alert animal.…”
Section: Generalmentioning
confidence: 99%